PENGARUH KARAKTERISTIK PERUSAHAAN DAN MEKANISME CORPORATE GOVERNANCE TERHADAP PENGUNGKAPAN RISIKO DALAM LAPORAN KEUANGAN INTERIM (Studi empiris pada perusahaan-perusahaan nonkeuangan yang terdaftar di Bursa Efek Indonesia) - Muhammad Andi Mubarok; Abdul Rohman (Diponegoro Journal of Accounting, 2013)
The purpose of this research is to provide empirical evidence about company characeristics such as sector type of industry, firm size, profitability, gearing, liquidity, and cross-listing, and then corporate governance mechanism such as institutional ownership, board size, board composition, and audit committe size that affect corporate risk disclosure in interim financial reports. The statistic method that used to test the hypotheses is multiple regression analysis. The population of this research are listed nonfinancial firms on IDX in 2011. Seventy eight nonfinancial firms listed on IDX in 2011 were chosen as sample. To explain the affects between the variables, agency and signalling theories were used. And then, corporate risk disclosure was measured with content analysis method. The results of this research show that only cross-listing and board size have significant positive effect on corporate risk disclosure.  In addition, the results do not support that institutional ownership, board composition and firm characteristics attributes (sector type of industry, firm size, profitability, gearing, and liquidity) have significant effect on corporate risk disclosure in interim financial reports.